Pelanggaran Nilai Moral dalam Komitmen Pernikahan: Film Wedding Agreement The Series dan Melur untuk Firdaus - Hartati, Rahma Dewi; Ananda, Refisa (Jurnal Sastra Indonesia, 2023)
This study aims to explain the violation of moral values in marriage commitments in the films Wedding Agreement the Series and Melur for Firdaus. The research method used is descriptive qualitative using content analysis. This research data is in the form of character dialogues in the films Wedding Agreement the Series and Melur for Firdaus. The results of this study show the phenomenon of moral values contained in the two films in the form of violations of marriage commitments depicted through the characterization of the characters Bian and Tari in the film Wedding Agreement the Series (Indonesia) with the characters Firdaus and Melur in the film Melur for Firdaus (Malaysia). Based on the analysis of the data it can be concluded that; 1) both films contain elements of violation of moral values, namely violation of marriage commitment in the form of the character's inability to uphold the promise of marriage 2) violation of norms that occurs due to the absence of emotional closeness between the characters as husband and wife, so that there is no passion to give or get physical and sexual satisfaction in the marriage which is reflected in the plot of the film